Generalization of the software "Gaining Words" for the acquisition of reading skill in primary education in the municipality of Jiguaní (Original) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The results of the generalization of the "Gaining words" software for five years at four elementary schools, and one of special education in Jiguaní are shown.  Aiming at  eliminating the deficiencies detected in the reading acquisition process. As a result of its application, it has been favored the acquisition of reading from an interactive work environment that responds to the characteristics of educational software systems, with a set of exercises related to the readiness and acquisition of reading stage in first grade, in which the graphemes studied at the different periods of the course are offered in a modular way, and the possibility of choosing any exercise within the selected module is also offered. With the generalization of the software, it was possible to detect the insufficiencies in the acquisition process of reading in primary schools, in the municipality of Jiguaní, constituting a way to optimize the development of the teaching process, and for a better preparation of schoolchildren in the contents of the different units of the readiness and acquisition stages of reading In the first grade.
Keywords: software; reading acquisition; primary education